'Trochars no more': Teaching chest drain insertion to remote and rural practitioners using a mobile skills unit. (July 2015) - Skinner, J.; Hardie, L.; Beasant, B.; Baker, A.; Ker, J.; O'neill, A.; Morse, J.
Abstract: Background : There are a number of approaches to teaching high-risk clinical skills, such as a large bore chest drain insertion, although effectiveness is limited and realism is only achieved at great expense. Summary of work : In response to a training needs' analysis of practitioners in remote and rural areas in Scotland, training in chest drains was identified as an urgent priority need. Subsequently, the Clinical Skills Managed Educational Network (CSMEN) developed an evidence-based multi-professional clinical skills pack. This e-learning resource encompasses all aspects of chest drain management, both pre and in-hospital. The pack and an interactive workshop is used to deliver 'blended' chest drain training on a mobile clinical skills unit. Evaluation confirms that the chest drain training is a valuable resource and has been widely used to deliver skills training in remote and rural areas. Feedback from all professional groups is positive. Conclusions : Developing shared national resources, with standardised workshops taught in local contexts via a mobile skills unit is one approach to the challenges associated with delivering high-risk clinical skills education.